The Apostolic Movement in Zimbabwe (A study of the Apostolic Faith Mission of South Africa (A.F.M.S.A.) and the Unity of African Apostolic Faith Church (U.A.A.F.C.) 1917-1985 ; topic - Mbuwayesango, Elias Munyaradzi; University of Zimbabwe History Department ((Harare), 1985)
This paper attempts to trace the development of a breakaway organization, the Vapository Movement in Zimbabwe, taking special note of the Parent Church which gave birth to the movement
Keywords: Apostolic Faith Mission of South Africa; Religion; Mission; Kirche; Simbabwe -- Religion -- Mission -- Christliche Kirche; Simbabwe; Forschungsbericht